Transfer of Lauric and Myristic Acid from Black Soldier Fly Larval Lipids to Egg Yolk Lipids of Hens Is Low. Issue 4 (22nd April 2021) - Heuel, Maike; Kreuzer, Michael; Sandrock, Christoph; Leiber, Florian; Mathys, Alexander; Gold, Moritz; Zurbrügg, Christian; Gangnat, Isabelle D. M.; Terranova, Melissa
Abstract: Implementing insects, such as the black soldier fly larvae (BSFL), as animal feed commonly includes the previous removal of substantial amounts of fat. This fat may represent an as yet underutilized energy source for livestock. However, transfer of lauric and myristic acid, prevalent in BSFL fat and undesired in human nutrition, into animal‐source foods like eggs may limit its implementation. To quantify this, a laying hen experiment was performed comprising five different diets (10 hens/diet). These were a control diet with soybean oil and meal and a second diet with soybean oil but with partially defatted BSFL meal as protein source. The other three diets were based on different combinations of partially defatted BSFL meal and fat obtained by two different production methods. Lauric acid made up half of the BSFL fat from both origins. Both BSFL fats also contained substantial amounts of myristic and palmitic acid. However, in the insect‐based diets, the net transfer from diet to egg yolk was less than 1% for lauric acid, whereas the net transfer for myristic and palmitic acid was about 30% and 100%, respectively. The net transfer did not vary between BSFL originating from production on different larval feeding substrates. The results illustrate that hens are able to metabolize or elongate very large proportions of ingested lauric acid and myristic acid, which are predominant in the BSFL lipids (together accounting for as much as 37 mol%), such that they collectively account for less than 3.5 mol% of egg yolk fatty acids.